Recent Development and Applications of Advanced Materials via Direct Ink Writing. Issue 7 (27th January 2022) - Tsang, Alpha Chi Him; Zhang, Jintao; Hui, Kwun Nam; Hui, Kwan San; Huang, Haibao
Abstract: Direct ink writing (DIW), a type of extrusion‐based 3D printing method, enables the rapid design and building of size‐ and shape‐scalable 3D structures in a low‐cost and green manner without the need for specific size reactors and secondary substrates compared to traditional synthesis methods. Coupling the use of sol‐gel inks with optimized rheological properties (elastoviscosity and shear stress) and a wide range of nanomaterials enhances the mechanical and electrical conductivity of printed products. In this review, the recent development in DIW methods, critical requirements for printable DIW inks, and applications of DIW‐printed products in medical, energy storage, and environmental treatment are reviewed. A perspective outlook associated with limitations from current DIW research is proposed for the breakthrough development of such technology in the future. Abstract : Advanced materials synthesis via 3D printing technology is reviewed, which focuses on direct ink writing (DIW). Background information of DIW, properties of the inks for DIW, and their applications in medical, energy storage and conversion, and photocatalytic applications are reviewed. Perspective outlook on the possible improvement and further development direction of DIW for advanced materials synthesis is proposed.